BEYOND THE SPICE: THE EARLY CONSUMPTION OF CINNAMON - Dissanayake, Dilhani (PEOPLE: International Journal of Social Sciences, 2020)
Cinnamon is an extraordinary commodity which has come to represent Sri Lankan culture far beyond its economic value. As a plant that is native to the island, cinnamon has a long-standing association with Sri Lankan culture and identity. Its unique aroma and medicinal and edible qualities have for centuries enabled it to capture the imaginations of individuals and empires. Cinnamon has been used as a multi-purpose spice due to its medicinal, preservative and edible qualities. The focus of this paper is an investigation of the early consumption of cinnamon around the world, beyond the shores of Sri Lanka. This study will provide a better understanding of cinnamon that goes beyond the cookery pot, whether as a spice in curries, or a flavour in baking. This discussion of cinnamon as something more than an attractive spice extends to comments about its cultural value and meaning, rather than its commercial value.